Sexual partner change and condom use among urban factory workers in northwest Tanzania. Issue 6 (December 1994) - Borgdorff, M W; Barongo, L R; Newell, J N; Senkoro, K P; Devillé, W; Velema, J P; Gabone, R M
Abstract : OBJECTIVE--To describe sexual partner change and condom use at the intake of a cohort study of urban factory workers in Tanzania. METHODS--From October 1991 to March 1992, 926 male and 170 female factory workers were interviewed using a structured, pre-coded questionnaire. Questionnaire reliability was assessed by pre-testing and comparison with results of unstructured interviews and carrying out repeat questionnaires on a sub-sample. RESULTS--Almost half of both men and women had had sexual intercourse by their 17th birthday. The period of premarital sex had an interquartile range of 2 to 10 years in men and 0 to 2.5 years in women. Having had sexual intercourse in the past month with more than one partner was reported by 22% of the men and 5% of the women. Factors associated with multiple partners in men were being born in or near Mwanza Region, having low education and low income, and being married. Condoms had been used in the past month by 3% only, mainly with casual partners. Condom use in men was associated with being young, living in town, being born in Kagera Region, high education and high income, being circumcised, and having causal or steady (non- martial) partners. CONCLUSION--Information, education and communication (IEC) on sexual relationships and condom use should start at an early age, and include education at primary schools. Much sexual partner change appears to occur through steady (non-marital) partnerships, indicating the need for IEC to be expanded beyond groups such as commercial sex workers and their clients.